Voting behavior of Kakus voters in P214 Selangau / Albert Kudang Ngadang and Mohd Khairie Ikmal Sulaiman - Ngadang, Albert Kudang; Sulaiman, Mohd Khairie Ikmal (2024)
This chapter focuses on the background ofthis study, which identifies the voting behaviour of Kakus voters in P214 Selangau during the previous 15th general election of Malaysia. This chapter begins with the background of the study, followed by the problem statement, research questions, research objectives, scope of the study, significance of the study, and finally the definition ofthe terms and concepts used in this study.